Pengaruh Latihan Push Up Normal dan Decline Push Up Terhadap Kemampuan Jump Servis pada Permainan Bolavoli Siswa SMAN 6 Jeneponto - Muh Yusril; Arimbi; Sudirman; Hasbunallah AS; Muh. Adnan Hudain (PT Mediatama Zayna Indonesia, 2024)
The purpose of the study was to determine the effect of normal push up training and decline push up training and the difference between normal push up training and decline push up training on jump serves in the SMAN 6 Jeneponto volleyball game. The sample in the study was 24 people. This research is an experimental study by giving jump serve tests in the form of pretests and posttests. Data analysis techniques using SPSS 25. The results of data testing obtained a t-count value of 5,000 and for the t-table obtained 1,795 and a significance value of 0.000 <α0.05, these results indicate that there is a significant difference. Because the t-count is greater than the t-table, so Ho is rejected, thus meaning that there is a significant effect of normal push up training on jump service ability. The results of data testing obtained a t-count value of 5,082 and for the t-table obtained 1,795 and a significance value of 0.000 <α0.05, these results indicate that there is a significant difference. Because the t-count is greater than the t-table, so Ho is rejected, thus it means that there is a significant effect of decline push up training on jump service ability. Based on the table above, the t-test has a post-test value between the normal push up training group and the decline push up training as follows. The results of data testing obtained a t-count value of 1,292 and for the t-table obtained 2,073 and a significance value of 0.210 greaterα = 0.05, Ho rejected H1 accept means there is a difference in jump serve between students who get normal push up training and decline push up training. Conclusion 1) there is a significant effect of normal push up training on jump serve ability. 2) There is a significant effect of decline push up training on jump serve ability. 3) There is a difference between normal push up training and decline push up training on the ability to jump serve in the ball game of SMAN 6 Jeneponto students.